Evidence against a cognitive advantage in the older bilingual population. Issue 6 (June 2019) - Papageorgiou, Andriani; Bright, Peter; Periche Tomas, Eva; Filippi, Roberto
Recent evidence has challenged long-standing claims that multi-language acquisition confers long-term advantages in executive function and may protect against age-related cognitive deterioration. We assessed evidence for a bilingual advantage in older monolingual and bilingual residents matched on age, gender, and socioeconomic status. A comprehensive battery of tests was administered to measure non-verbal reasoning, working memory capacity, visuo-spatial memory, response inhibition, problem solving, and language proficiency. Analyses, including Bayes factors, revealed comparable performance in both groups, with no significant differences on any task (and the only trend, found for the Tower of London task performance, indicated a monolingual advantage). Overall, therefore, our findings run counter to the bilingual advantage hypothesis. We consider the implications of our study and offer suggestions for future work in this area.